Common fixed points versus invariant approximation for noncommutative mappings - Nashine, Hemant Kumar (Rev. Anal. Numér. Théor. Approx., 2008)
The aim of this paper is to obtain common fixed points as invariant approximation for noncommuting two pairs of mappings. As consequences, our works generalize the recent works of Nashine [9] by weakening commutativity hypothesis and by increasing the number of mappings involved.